PELANGGARAN HAK MORAL DAN HAK EKONOMI PENCIPTA NASKAH FILM (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 305K/PDT.SUS-HKI/2014) - BISMAR SIREGAR (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Saidin2. T. Keizerina Devi A3. Jelly Leviza Cinematography or movie in Copyright Act is one of the components which is protected by Copyright Act. A lot of movies which are originated from a historical or famous figure arouse complex juridical problems. Biographical movie which comes from a show/performance is the outcome of an interesting creation to be analyzed to find out whether it is artificial or original. Since the object of the research is a movie or cinematography in Copyright Act, it is necessary to determine who the writer of that movie is.Keywords : Violation, Moral and Economic Rights, Writer